2000
DOI: 10.3109/10428190009059278
|View full text |Cite
|
Sign up to set email alerts
|

Alterations ofP53andRBGenes and the Evolution of the Accelerated Phase of Chronic Myeloid Leukemia

Abstract: Using the single-strand conformation polymorphism and heteroduplex analyses, the P53 and RB genes were analyzed in cell samples from twenty-eight patients with chronic myeloid leukemia (CML) both at diagnosis and at the onset of accelerated phase (AP) of the disease. No alterations of the P53 or RB genes were found in any of the chronic phase (CP) samples. Structural abnormalities of the P53 gene were observed in ten of twenty-eight AP samples within exons 4, 5, 7 and 9. Of the ten cases of AP disease with alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…A number of tumor suppressor genes are inactivated or downregulated by BCR-ABL in Ph + leukemia, including protein phosphatase 2 (21), p53 (22) and phosphatase and tensin homolog (23). The results of the present study revealed that the tumor suppressor, PDCD4, is also downregulated in CML patients and is negatively correlated with BCR-ABL expression.…”
Section: Discussionsupporting
confidence: 48%
“…A number of tumor suppressor genes are inactivated or downregulated by BCR-ABL in Ph + leukemia, including protein phosphatase 2 (21), p53 (22) and phosphatase and tensin homolog (23). The results of the present study revealed that the tumor suppressor, PDCD4, is also downregulated in CML patients and is negatively correlated with BCR-ABL expression.…”
Section: Discussionsupporting
confidence: 48%
“…Some tumor suppressor genes have been shown to be inactivated or down-regulated by BCR-ABL in Ph ϩ leukemia, including PP2A, 34 p53, 35 RB, 35 and interferon consensus sequence-binding protein. 36 In this study, we show that the tumor suppressor Pten is also down-regulated by BCR-ABL and that overexpression of Pten BLOOD, 21 JANUARY 2010 ⅐ VOLUME 115, NUMBER 3 For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…[161][162][163] A unifying mechanism for disease progression in CML As discussed, CML-BC is characterized by several seemingly incoherent chromosomal and molecular abnormalities. Yet, some generalizations can be attempted: (1) the vast majority of secondary changes involve genes encoding nucleus-localized proteins that directly or indirectly regulate gene transcription; (2) mutations/loss of function of tumor suppressor genes is predominant over mutation/activation of oncogenes; and (3) p53 is genetically or functionally inactivated in a large fraction of CML-BC cases.…”
Section: Role Of Molecular Abnormalities In CML Disease Progressionmentioning
confidence: 99%